The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1140/epjb/s10051-021-00245-1
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity-mediated analysis of the transverse-field XY chain with the long-range interactions: anisotropy-driven multi-criticality

Abstract: The transverse-field XY spin chain with competing antiferromagnetic long-range interactions, J r ∝ 1/r α (r: distance between spins), and the exponent α was investigated numerically. The main concern is to clarify the character of the transversefield-driven phase transition for the small-α regime around the XX-symmetric point, η = 0 (η: XY -anisotropy parameter). To cope with the negative-sign problem, we employed the exact-diagonalization method, which enables us to evaluate the fidelity susceptibility χ F . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…In Ref. [307], the QPT of the anisotropic LRTFAXYM was studied with exact diagonalisation, and the critical point was determined for β = 1/2, which coincides perfectly with the value from pCUT+MC (see Figure 31). For all β > 0, Adelhardt et al [31] identified the same three regimes for the universality of the QPT as for the ferromagnetic LRTFIM.…”
Section: Ferromagnetic Anisotropic Long-range Xy Chain In a Transvers...mentioning
confidence: 56%
See 2 more Smart Citations
“…In Ref. [307], the QPT of the anisotropic LRTFAXYM was studied with exact diagonalisation, and the critical point was determined for β = 1/2, which coincides perfectly with the value from pCUT+MC (see Figure 31). For all β > 0, Adelhardt et al [31] identified the same three regimes for the universality of the QPT as for the ferromagnetic LRTFIM.…”
Section: Ferromagnetic Anisotropic Long-range Xy Chain In a Transvers...mentioning
confidence: 56%
“…[31], and the data point "ED" is from Ref. [307]. The anisotropy parameter β is tuned from β = 1 (Ising) to β = 0 (isotropic XY).…”
Section: Ferromagnetic Anisotropic Long-range Xy Chain In a Transvers...mentioning
confidence: 99%
See 1 more Smart Citation